INDUSTRIAL ORGANIZATION OF THE MARITIME SEISMIC ACQUISITION MARKET - Barros, Paulo; Ferreira, Hamilton; Lemos, Mauro (International Journal For Research In Business, Management And Accounting, 2023)
In this article, we analyze the industrial organization of the Maritime Seismic Acquisition Market (MSAM). Their firms are process, science, and technology intensive and provide geophysical information for oil companies operating in the upstream offshore segment. Our objective is to find the determinants of price changes and their relationships with market structures, firms conduct, and performance (SCP), considering the effect of oil price volatility on MSAM demand. To achieve this objective, we use a theoretical framework of the Industrial Organization (IO) to analyze the empirical data of MSAM at a global database between 2006 and 2019. The research is structured to calculate the SCP and the New Empirical IO (NEIO) parameters related to concentration, market power, and competition. We can verify the hypothesis about market power or collusion from empirical demand and cost models. We found that the concentration levels and the supplier’s profit in MSAM decrease to an increase in demand, for which positive fluctuations are supplied by firms in the market fringe, generating pressure on the average costs of the industry, an essential factor to explain the price increase during periods of market heating. Although MSAM has a concentration, its firms have low levels of market power and markups with a high degree of competition, configuring itself as a Competitive Oligopoly.